A Case of Cryptococcal Meningitis in Hiv positive patient in A tertiary care hospital in Kancheepurum district, Tamilnadu, India - Shanthi Banukumar; I Kannan (International Journal of Medical Research and Review, 2015)
MeningitisCryptococcal meningitis has been reported in recent years as major life threatening opportunistic infection associated with HIV with a leading cause of mortality ranging from 7 – 15 % around the world & 6% in United States of America. Approximately 25 – 30 % overall mortality rate is encountered in patients suffering from Cyrptococcal meningitis. Among the survivors 40% have significant neurological disorders like loss of vision, decreased mental function, hydrocephalus, cranial nerve palsies with relapse occurring in 25% of cases. It frequently presents as subacute meningitis and is a sporadic infection that affects both immunosuppressed patients (50%) and nonimmunosuppressed patients. This is the first case of cryptococcal meningitis reported in our Hospital in a HIV positive patient reported in our area – Rathinamangalam – Kancheepuram district – during a span of 2 years case study 2013 to 2014.